2016
DOI: 10.1111/ctr.12836
|View full text |Cite
|
Sign up to set email alerts
|

Allograft biopsy findings in patients with small bowel transplantation

Abstract: In this study, we sought to determine the incidence of post-transplant complications including acute cellular rejection (ACR), infection, and post-transplant lymphoproliferative disease (PTLD) in mucosal allograft biopsies in patients with small bowel transplant at our institution. We retrospectively reviewed pathology reports from 5675 small bowel allograft biopsies from 99 patients and analyzed the following: indications for biopsy, frequency and grade of ACR, the presence of infectious agents, results of wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…As there is continual exchange of cells and antigens during congenital and acquired immune function, T cell-mediated acute cellular rejection[25] and antibody-mediated humoral rejection[26] are very likely to occur after small bowel transplantation. Studies have demonstrated that after small bowel transplantation, even under the application of a conventional immunization regimen, the incidence of rejection remains high[27,28]. The need to find a better method for induction of immune tolerance or transplantation rejection, has led to studies exploring whether BMMSCs can inhibit rejection after small bowel transplantation[29].…”
Section: Discussionmentioning
confidence: 99%
“…As there is continual exchange of cells and antigens during congenital and acquired immune function, T cell-mediated acute cellular rejection[25] and antibody-mediated humoral rejection[26] are very likely to occur after small bowel transplantation. Studies have demonstrated that after small bowel transplantation, even under the application of a conventional immunization regimen, the incidence of rejection remains high[27,28]. The need to find a better method for induction of immune tolerance or transplantation rejection, has led to studies exploring whether BMMSCs can inhibit rejection after small bowel transplantation[29].…”
Section: Discussionmentioning
confidence: 99%
“…Out of a total of 472 patients, 56 patients (11.9%) had gastric PTLD while 415 patients (88.1%) had PTLD in other locations[ 13 ] (Table 1 ). The small bowel is another common area of involvement, PTLD of the small bowel was diagnosed in 50% of patients having PTLD after small bowel transplantation (SBT)[ 14 ]. In patients requiring surgery for GI-PTLD complications, organ involvement varied: Small bowel (50%), proximal right colon (31.2%), and stomach, duodenum, and transverse colon (6.2%)[ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, mechanical failure of the graft due to operation during surgery may occur during the early phase after transplantation. Cytomegalovirus (CMV) enteritis and Epstein-Barr virus -related enteritis are severe side effects and post-transplantation lymphoproliferative disorders/diseases [13][14][15]. It is often difficult to make a differential diagnosis of the ACR findings.…”
Section: Current Status Of Small Bowel Transplantationmentioning
confidence: 99%